PENGARUH JUMLAH ANGGOTA, MODAL LUAR, DAN TOTAL ASSET TERHADAP SISA HASIL USAHA (Studi Empiris pada Koperasi Simpan Pinjam di Kota Tasikmalaya tahun 2016) - Sudaryanti, Dedeh Sri (Universitas Dr. Soetomo, 2017)
SHU of cooperative business is usually used as a measure of the welfare of members. There are many factors that influence the acquisition of SHU cooperatives. This research was conducted to know and analyze the partial and simultant influence of Total Member, Outside Capital and Total Asset to SHU at savings and loan cooperative which is in Tasikmalaya city. The population in this research is all the savings and loan cooperatives recorded in the Office of Cooperatives, Small and Medium Enterprises, Industry and Trade Tasikmalaya City in 2016. Selected 53 research samples by using purposive sampling technique. Based on the data analysis and discussion of research results found evidence that partially Total Member and Outside Capital has no significant effect to SHU, while Total Asset has a significant positive effect on SHU, which means the increase of Total Asset a savings and loan cooperative will result in increasing the SHU. Simultaneously The Number of Members, Outside Capital, and Total Asset Affects the SHU. Keywords: SHU, number of members, external capital, total assets